Implementasi Cyber PR dalam Customer Relationship Management bagi Pelaku UMKM Sebagai Strategi Bertahan di Masa Pandemi 2020-2021 - Putri, Martina Shalaty; Hasanuddin, Yuan Maulana (Universitas Mercu Buana, 2021)
The Covid-19 pandemic has attacked not only the health sector but also the economic sector. One of the efforts to recover the economy is to encourage the MSME sector to survive. Tour and Travel Revolution (TTR) is one of the outstanding MSMEs which is a travel company that has experienced a very negative impact from the 2020-2021 pandemic. With utilizing Cyber PR through CRM this company can survive and form a new business engaged in courier services under the name Multi Kurir. This study wants to see how the implementation of Cyber PR in Customer Relations Management (CRM) for MSMEs, especially the Tour and Travel Revolution as a strategy to survive in the 2020-2021 Pandemic. The research method used is descriptive qualitative. The results obtained are, the management of cyber PR and CRM is carried out properly, technology which is the main point in the success of the tour and travel form a new business named PT Multi Kurir. With managing merchant data using website, social media and WhatsApps application.